Male gender role strain as a barrier to African American men’s physical activity - Griffith, Derek M. (Health Educ Behav, 2011)
Despite the potential health consequences, African American men tend to treat their roles as providers, fathers, spouses, and community members as more important than engaging in health behaviors such as physical activity. We conducted 14 exploratory focus groups with 105 urban, middle-aged African American men from the Midwest to examine factors that influence their health behaviors. Thematic content analysis revealed three interrelated barriers to physical activity: (a) work, family, and community commitments and priorities limited time and motivation for engaging in physical activity; (b) physical activity was not a normative individual or social activity and contributed to men prioritizing work and family responsibilities over physical activity; and (c) the effort men exerted in seeking to fulfill the provider role limited their motivation and energy to engage in physical activity. These findings highlight the need for physical activity interventions that consider how health fits in the context of men’s overall lives.